2019
DOI: 10.1038/s41419-019-1860-2
|View full text |Cite
|
Sign up to set email alerts
|

The NEDD8-activating enzyme inhibitor MLN4924 sensitizes a TNFR1+ subgroup of multiple myeloma cells for TNF-induced cell death

Abstract: The NEDD8-activating enzyme (NAE) inhibitor MLN4924 inhibits cullin-RING ubiquitin ligase complexes including the SKP1-cullin-F-box E3 ligase βTrCP. MLN4924 therefore inhibits also the βTrCP-dependent activation of the classical and the alternative NFĸB pathway. In this work, we found that a subgroup of multiple myeloma cell lines (e.g., RPMI-8226, MM.1S, KMS-12BM) and about half of the primary myeloma samples tested are sensitized to TNF-induced cell death by MLN4924. This correlated with MLN4924-mediated inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The small molecule MLN4924 (Pevonedistat), an adenosine sulfamate analog, potently and selectively inhibits NEDD8 activating enzyme (NAE), the E1 enzyme 14 . MLN4924 inhibits several solid and liquid cancers in vitro and in vivo [14][15][16][17][18] , and Phase 1 clinical trials demonstrated good systemic tolerance and some efficacy [19][20][21] . NAE is a dimer of NAE1 and ubiquitin-like modifier activating enzyme 3 (UBA3).…”
Section: Introductionmentioning
confidence: 99%
“…The small molecule MLN4924 (Pevonedistat), an adenosine sulfamate analog, potently and selectively inhibits NEDD8 activating enzyme (NAE), the E1 enzyme 14 . MLN4924 inhibits several solid and liquid cancers in vitro and in vivo [14][15][16][17][18] , and Phase 1 clinical trials demonstrated good systemic tolerance and some efficacy [19][20][21] . NAE is a dimer of NAE1 and ubiquitin-like modifier activating enzyme 3 (UBA3).…”
Section: Introductionmentioning
confidence: 99%
“…Our study found that TNFR1 expression is upregulated by HRG overexpression. Cellular TNFR1 level is reported to be correlated with sensitivity to MLN4924/TNF-induced cell death in multiple myeloma 43 . Increased sensitivity of HCC cells to 5-fluorouracil-induced apoptosis was found with HRG overexpression which enhanced TNFR1 protein stability in the present study, pointing out a possibility that ways to upregulate HRG expression may become an adjuvant approach for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Neddylation of the cullin subunit is driven by the NEDD8-activating enzyme (NAE). Blockade of neddylation can be achieved by selectively inhibiting NAE with a small molecule inhibitor MLN4924 (also known as pevonedistat) [ 24 ]. We observed that the incubation of hippocampal slices with MLN4924 prior to the induction of cLTP significantly inhibited ATF4 degradation during LTP.…”
Section: Discussionmentioning
confidence: 99%